Integration of travel agencies with other supply chain members - Topolšek, Darja (Logistics and sustainable transport, 2016)
The performance of tourism supply chains depends on the efficiency of all members involved, including the travel agencies. The paper addresses the analysis of relationships between the agencies' external integration with other supply chain members on one side, and the efficiency of the agencies on the other. The data envelopment analysis is applied for the estimation of efficiencies, while the structural equation modelling (SEM) is conducted for identification of possible integration impacts on the efficiency. Results show that integration with other supply chain members indeed has some positive impacts on the agencies' efficiency. Also, the developed SEM model implies that in-depth forms of collaboration would enable more effective exploitation of the identified relations between the integration and efficiency of the agencies. This finding could be an important guideline for the agencies' management in the sense of achieving more satisfied customers and bigger profits, as well as reduced operational costs.
Keywords: efficiency; external integration; logistics; logistika; oskrbovalne verige; structural equation modeling; strukturno modeliranje enačb; supply chains; tourism sector; travel agencies; turistične agencije; turistični sektor; učinkovitost; zunanja integracija